Challenging the Uniformity Myth in Career Counseling Outcome Studies: Examining the Role of Clients' Initial Career Counseling Goals. (February 2017) - Verbruggen, Marijke; Dries, Nicky; Van Laer, Koen
This study aimed to challenge the "uniformity myth" in career counseling outcome studies—that is, a tendency toward studying career counseling clients as homogenous, implicitly assuming that the same outcomes would be beneficial to all clients. To this end, we examined the role of clients' initial career counseling goals. We hypothesized that a client's career counseling goals would affect (1) which outcomes the client is likely to attain through career counseling and (2) which outcomes he or she would most benefit from (in terms of improved well-being). Hypotheses were tested using data from a three-wave study with Flemish adult career counseling clients. We included six potential career counseling goals and corresponding outcomes: (1) increasing self-awareness, (2) increasing opportunity awareness, (3) making a career decision, (4) finding a new job, (5) improving work–family balance, and (6) improving work relationships. We found that clients were more likely to attain outcomes that matched their initial career counseling goals and less likely to attain other outcomes. In addition, goal attainment (i.e., the attainment of outcomes that match a client's initial goals)—but not nongoal attainment (i.e., the attainment of outcomes that do not correspond to a client's initial goals)—related to clients' subsequent career and life satisfaction. Implications for career counseling research and practice are discussed.